SAINS SEBAGAI JEMBATAN DIALOG PERADABAN : STUDI KASUS ANDALUSIA SEBAGAI PUSAT TRANSFER ILMU ISLAM KE EROPA - Ircham Fahim Firori; Zainuddin Fanani (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This research examines Andalusia's role as a centre of knowledge transfer between the Islamic world and Europe during its heyday (8th-15th centuries). Through cities such as Córdoba, Toledo and Granada, Andalusia became not only a place for the translation of scientific works, but also a space for collaboration between Muslim, Christian and Jewish scholars. The translation process undertaken by figures such as Gerard of Cremona and Michael Scot introduced scientific thought from the Islamic world, including the works of Ibn Sina and Al-Khwarizmi, into the European educational curriculum. The research is a study of documentary data collection methods and analysis using content analysis. This research shows that intercultural interaction in Andalusia created a dialogue that strengthened interreligious tolerance and understanding, and contributed to Europe's intellectual Renaissance during the Renaissance. The findings are relevant to contemporary society, emphasising the importance of intercultural collaboration in promoting scientific progress and creating an inclusive and harmonious civilisation.